Soviet policy in the far East 1944 - 1951 - Beloff, Max. (London, 1956)
This book is an expansion of a paper which I was invited to T contribute to the Conference of the Institute of Pacific Relations held at Lucknow in October 1950. Mr. W. L. Holland, Secretary-General of the Institute of Pacific Relations, suggested that a more detailed and documented study of the subject would be of wider interest and I am grateful to him and to the Institute of Pacific Relations for the suggestion and for the assistance given to the project. I also owe a real debt of gratitude to the Royal Institute of International Affairs for making its resources available to me at all stages in the pre paration of the book, and in this connexion in particular to Miss Margaret Cleeve, O.B.E., Research Secretary of the Institute.
Keywords: International Relations - 1944-1951